Determination of fluoroacetate and fluoride in blood serum by capillary zone electrophoresis using capacitively coupled contactless conductivity detection - Rajh Vidal, Denis Tadeu; Augelli, Marcio Antonio [UNESP]; Hotta, Guilherme Minoru; Lopes, Fernando Silva; do Lago, Claudimir Lucio (Wiley-Blackwell, 2011)
Fluoroacetate is a highly toxic species naturally found in plants and in commercial products (compound 1080) for population control of several undesirable animal species. However, it is non-selective and toxic to many other animals including humans, and thus its detection is very important for forensic purposes. This paper presents a sensitive and fast method for the determination of fluoroacetate in blood serum using capillary electrophoresis with capacitively coupled contactless conductivity detection. Serum blood samples were treated with ethanol to remove proteins. The samples were analyzed in BGE containing 15 mmol/L histidine and 30 mmol/L gluconic acid (pH 3.85). The calibration curve was linear up to 75 mu mol/L (R(2) = 0.9995 for N = 12). The detection limit in the blood serum was 0.15 mg/kg, which is smaller than the lethal dose for humans and other animals. Fluoride, a metabolite of the fluoroacetate defluorination, could also be detected for levels greater than 20 mu mol/L, when polybrene was used for reversion of the EOF. CTAB and didecyldimethylammonium bromide are not useful for this task because of the severe reduction of the fluoride level. However, no interference was observed for fluoroacetate.
Keywords: Blood serum; Capacitively coupled contactless conductivity detection; Compound 1080; Fluoride; Fluoroacetate